If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H * 3 = -12 Reorder the terms for easier multiplication: 3H = -12 Solving 3H = -12 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Divide each side by '3'. H = -4 Simplifying H = -4
| 8y+5y+7z-3x+4z-6y= | | 3y+7(2y+1)= | | 4(3x+3)+3x+1=5 | | 5x-16=2(2x-3) | | -2(3x+7)=-9x | | 53-8x+x^2+5x+39=180 | | 5(5-2)-8=3K-(2k-3) | | 0=n-2-3n | | 5(x)+(5x)= | | 8-2(-7x+6)=13 | | 2q=x-13 | | 7+2b=53 | | (5x+3)22(3x-5)= | | -5-5y=30 | | 540+13.50x=4158 | | -3f+9f=15 | | -14=-4b+6b | | -14=-4b | | 4x+15=8x+23 | | 5+bx=3x+ax | | 12x-8=7x-7 | | -8=-6+x-x | | -30-3y=-21 | | 21-8+3*12= | | 5x+3x=77 | | 7.74*5= | | 4x+25=124 | | 7x+3y=48 | | X^4-15x^2+-16=0 | | ax+3x=bx+5 | | -4x+5=4x+-4 | | 4b-13=3 |